Novel natural product based anti-anxiety therapy and natural insecticides - Puniani, Evaloni Takavaha (University of Ottawa (Canada), 2004)
The EtOH extracts of the leaves of Margraviaceae, a relatively rare Central American vine for which ethnobotanical reports suggested possible anti-anxiety properties, showed significant anti-anxiety activity in animal models for anxiety. Subsequent bioassay-guided fractionation of these extracts yielded an EtOAc active fraction (f1). Further bioassay-directed chromatography of (f1), led to the isolation of betulinic acid (3) as the bioactive constituent in 0.01% of dry weight. Six known pentacyclic triterpenoids [( 1a), (1b), (2a), (2b), ( 4), (5a)], six known flavonoids [(6), ( 7), (8a), (8b), (9), ( 10)], chondrillasterol (11), linolenic acid (12 ) and a porphyrin type compound (13) were also isolated. When (3) was administered at 0.5 mg per kg (possibly less) in a variety of rat and mouse model assays, the activity of (3) was comparable to that of Valium, the most famous member of the benzodiazepines family. Synthetic derivatives of (3) were prepared and evaluated for anti-anxiety activity. Several of the simple esters appear to have ideal properties as new drug Candidates. In particular, betulinic acid methyl ester or methyl betulinate (3a) exhibited anti-anxiety activity superior to (3). The activity profile of (3a) is such that (3a) can be considered a viable drug candidate. An excellent relay synthesis of (3) from another closely related natural product betulin (14), that is abundantly available in Eastern Ontario, was developed. Radioactive 3H-labelled betulinic acid methyl ester ( 3a″) was also prepared in order to facilitate identification of relevant anti-anxiety receptors and the mechanism of action of the compound. This is important since (3) showed no significant binding to any of the 40 anti-anxiety receptors currently implicated in anxiety. Therefore, it appears to act as an anti-anxiety agent via a new mode of action.* In a second project, the active components of a member of the Piperaceae or Pepper family (P. tuberculatum) from Costa Rica, were isolated and their structures characterized as 5,6-dihydropiperlonguminine (25), 5,6-dihydropiperine (26), piperine ( 27) and piperlonguminine (28). Extracts from this neotropical plant had been previously demonstrated by our biology collaborators, Professor Arnason's group, to be strongly insecticidal towards a variety of pests including mosquitoes, earwigs and white grubs. Moreover, the P. tuberculatum extracts were as effective as the well-documented Asian (P. nigrum) and African ( P. guineense) Piper species. Piperamides (25)--(28) were synthesized in sufficient amounts to allow extensive evaluation of their insecticidal properties. Experiments with these piperamides showed that the tertiary and quaternary mixtures have greater-than-additive toxicity compared to single compounds or binary mixtures. That is, these piperamides synergize each other. Compound (25) was the most acutely toxic in mosquito larvae bioassays. The field trials to date indicate a high potential for the development of an effective, relatively inexpensive botanically based insecticide. Radioactive 3H-labelled piperine (27″ ) was also synthesized for toxicokinetic studies. *Please refer to dissertation for diagrams.
Keywords: Chemistry, Pharmaceutical.; Chemistry, Agricultural.